Modern‐day cardio‐oncology: a report from the 'Heart Failure and World Congress on Acute Heart Failure 2018'. (20th December 2018) - Anker, Markus S.; Lena, Alessia; Hadzibegovic, Sara; Belenkov, Yury; Bergler‐Klein, Jutta; de Boer, Rudolf A.; Cohen‐Solal, Alain; Farmakis, Dimitrios; von Haehling, Stephan; López‐Fernández, Teresa; Pudil, Radek; Suter, Thomas; et al.
Abstract: During the 'Heart Failure and World Congress on Acute Heart Failure 2018', many sessions and lectures focused on cardio‐oncology. This important field of research is constantly growing, and therefore, a great amount of time during the congress focused on it. Prevention and early recognition of side effects is very important in cancer patients. One of the most common and potentially severe problems during antineoplastic therapy is cardiotoxicity. Hence, cardio‐oncology is vital in managing cancer patients. This paper will summarize the topics discussed in three main sessions and many additional lectures throughout the 'Heart Failure and World Congress on Acute Heart Failure 2018'. The covered topics included pathophysiological mechanisms in the development of heart failure, risk factors, and early signs of cardiotoxicity detectable with different circulating and imaging biomarkers, as well as cardioprotective treatments recommended by different guidelines and position papers.